2017
DOI: 10.3174/ajnr.a5257
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and Spatial Variances in Arterial Spin-Labeling Are Inversely Related to Large-Artery Blood Velocity

Abstract: BACKGROUND AND PURPOSE:The relationship between extracranial large-artery characteristics and arterial spin-labeling MR imaging may influence the quality of arterial spin-labeling-CBF images for older adults with and without vascular pathology. We hypothesized that extracranial arterial blood velocity can explain between-person differences in arterial spin-labeling data systematically across clinical populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 36 publications
6
17
1
Order By: Relevance
“…That study did not measure arterial diameter, so a change in blood flow despite no change in velocity cannot be ruled out. The lack of a change in velocity, however, is consistent with our finding of no change in sCoV, given the relationship between sCoV, blood flow velocity and arterial transit time (Mutsaerts et al, 2017 ; Robertson et al, 2017 ). Spatial CoV of ASL with a single post-label delay is a heuristic index of arterial transit time (Mutsaerts et al, 2017 ), whereby a prolonged transit time leads to greater spatial variation of intensities within the CBF image.…”
Section: Discussionsupporting
confidence: 90%
“…That study did not measure arterial diameter, so a change in blood flow despite no change in velocity cannot be ruled out. The lack of a change in velocity, however, is consistent with our finding of no change in sCoV, given the relationship between sCoV, blood flow velocity and arterial transit time (Mutsaerts et al, 2017 ; Robertson et al, 2017 ). Spatial CoV of ASL with a single post-label delay is a heuristic index of arterial transit time (Mutsaerts et al, 2017 ), whereby a prolonged transit time leads to greater spatial variation of intensities within the CBF image.…”
Section: Discussionsupporting
confidence: 90%
“…Our results suggest that cerebral hemodynamic alterations represent a useful element in assessing AD profiles, independent of structural, amyloid burden, or glucose uptake abnormalities. A recent study found that extracranial blood velocity is inversely related to ASL sCoV; which unfortunately was not possible to evaluate in the current study because phase contrast angiography from external arteries was not collected. Future studies are required to disambiguate large‐artery from small‐vessel hemodynamic influences on the ASL sCoV metric.…”
Section: Discussionmentioning
confidence: 82%
“…the spatial coefficient of variation (CoV) of CBF images) as a region-of-interest (ROI)-based surrogate measure for prolonged ATT. 27,28 A study of subjects with hypertension showed that spatial CoV, which is calculated from the standard deviation in an ROI divided by the ROI mean in single-PLD pCASL images, is strongly correlated with ATT measured by flow encoding arterial spin tagging (FEAST). 27 Another study of healthy adults and patients with cerebrovascular disease reported that spatial CoV from single-PLD pCASL images is inversely correlated with extracranial arterial blood velocity measured by phase-contrast MR imaging.…”
Section: Introductionmentioning
confidence: 99%